Expert One-on-One Visual Basic .NET Business Objects - Lhotka, Rockford (Apress, 2012)
This book is about application architecture, design, and development in .NET, using object-oriented concepts. Specifically, we'll be building business-focused objects called business objects, and we'll be implementing them in various distributed environments that include web and client-server configurations. To this end, we'll be making use of a great many .NET technologies, object-oriented design and programming concepts, and distributed architectures.